2004
DOI: 10.1074/jbc.m312448200
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Nfs1p Is Involved in Thio-modification of Both Mitochondrial and Cytoplasmic tRNAs

Abstract: The IscS protein is a pyridoxal phosphate-containing cysteine desulfurase involved in iron-sulfur cluster biogenesis. In prokaryotes, IscS is also involved in various metabolic functions, including thio-modification of tRNA. By contrast, the eukaryotic ortholog of IscS (Nfs1) has thus far been shown to be functional only in mitochondrial iron-sulfur cluster biogenesis. We demonstrate here that yeast Nfs1p is also required for the post-transcriptional thio-modification of both mitochondrial (mt) and cytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
111
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 46 publications
5
111
0
Order By: Relevance
“…tRNA Extraction and Gel Retardation Analysis of the Thiomodification of tRNA-The total tRNAs of the yeast cells were prepared as described previously (3). The plant seedlings were grown on Murashige and Skoog plates for 3 weeks, and tRNAs were extracted using the PureLink miRNA Isolation kit (Invitrogen).…”
Section: Plant and Yeast Strains Plasmids Media And Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…tRNA Extraction and Gel Retardation Analysis of the Thiomodification of tRNA-The total tRNAs of the yeast cells were prepared as described previously (3). The plant seedlings were grown on Murashige and Skoog plates for 3 weeks, and tRNAs were extracted using the PureLink miRNA Isolation kit (Invitrogen).…”
Section: Plant and Yeast Strains Plasmids Media And Growthmentioning
confidence: 99%
“…The molecular mechanisms for tRNA thio-modification in eukaryotic cells have primarily been studied using yeast, especially Saccharomyces cerevisiae. In the yeast S. cerevisiae, cytosolic and mitochondrial tRNAs are thio-modified by partially overlapping multistep mechanisms in which several cytosolic and mitochondrial proteins participate (3)(4)(5)(6)(7). A common initial step for these thiomodifications involves the mitochondrial cysteine desulfurase Nfs1, which cleaves sulfur from its substrate cysteine to form the enzyme-bound cysteinyl persulfide intermediate (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of components in the ISC biogenesis pathway for thio modification of eukaryotic tRNAs has so far mainly been analyzed in yeast (15,16). In the present study we have extended this analysis to the parasitic protozoa T. brucei.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, the same appears to be the case for the corresponding mitochondrial encoded tRNAs (14). Recent work in the yeast Saccharomyces cerevisiae has shown that thiolation of tRNAs depends on components of the Fe/S cluster (ISC) biogenesis pathway (15)(16)(17). ISCs of iron-sulfur proteins are essential for a wide variety of cellular processes, and their assembly requires complex and interconnected machineries that are localized in both mitochondria and the cytosol (17).…”
mentioning
confidence: 99%